DESIGN, SYNTHESIS, DOCKING, ANTITUMOR SCREENING, AND ABSORPTION, DISTRIBUTION, METABOLISM, AND EXCRETION PREDICTION OF NEW HESPERDIN DERIVATIVE - AL-SHMGANI, HANADY S; RAIED MUSTAFA SHAKIR; AHMED W NASER; ELEKOFEHINTI, OLUSOLA OLALEKAN (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: Hesperidin (HSP) is a pharmacologically active organic compound found in citrus fruits and peppermint. We synthesized a new HSP derivative by reacting it with 5-Amino-1,3,4-thiadiazole-2-thiol in acetic acid. Methods: This compound was characterized by Fourier-transform infrared, proton nuclear magnetic resonance, and electron impact mass spectra. A molecular docking study explores the predicted binding of the compound and its possible mode of action. Bioavailability, site of absorption, drug mimic, and topological polar surface was predicted using absorption, distribution, metabolism, and excretion (ADME) studies. Results: The docking study predicts that the new compound binds to the active sites of Aurora-B and the MST3 pocket and has good ADME properties. Moreover, the thiazole ring and the presence of the electron releasing groups and hydrogen bond interaction with amino acid residues within the active sites play an important role in enhancing the antioxidant activity. Conclusion: In the present study, a new HSP derivative has been synthesized and characterized successfully and a theoretically promising antioxidant and anticytotoxic active agent introduced. We have shown the detailed binding analysis of 1,3,4-thiadiazol and hydrogen bonds with the inhibitor binding cavity of Aurora B and MST3. This could provide the development of some effective compounds against different diseases.